Acoustics of an assembly of anurans in the geographical Cauca River Valley, Colombia - Mejía-Cepeda, Natalia; Murillo-García, Óscar; Bolívar-García, Wilmar (Revista de Biología Tropical, 2024)
Introduction: Acoustic communication is essential in anuran communities, particularly for reproduction. However, the acoustic space is limited, and bioacoustic interferences, such as competition for mating and resources, impact the effectiveness of communication. The tropical dry forest in Colombia hosts resilient anuran species that have endured significant reduction, fragmentation, and transformation over the past decades. The scarce research on this topic underscores the importance of acoustically characterizing anuran assemblages to understand species coexistence, monitor changes in the community, and evaluate the impact of both invasive species and human activity on the ecosystem. Objective: To acoustically characterize an anuran assemblage in the Cauca River Valley. Methods: From September to November 2022 (rainy season), acoustic recordings were obtained using passive and active acoustic sensors from an anuran community in the geographical Cauca River Valley, on the western flank of the Central Cordillera in Colombia. Anuran advertisement calls were analyzed in three dimensions: spectral parameters, temporal patterns, and acoustic activity. Results: Five anuran species were recorded, exhibiting high overlap in activity but significant structural differences in their calls. The species were predominantly nocturnal, except for one from the dendrobatid family. Conclusions: Each species presents a distinct acoustic niche, avoiding overlap in acoustic signals. These findings establish a baseline for assessing future changes in the assemblage.